Real-World Goal Setting and Use of Outcome Measures According to the International Classification of Functioning, Disability and Health: A European Survey of Physical Therapy Practice in Multiple Sclerosis - Řasová, Kamila; Martinková, Patrícia; Soler, Bernadita; Freeman, Jenny; Cattaneo, Davide; Jonsdottir, Johanna; Smedal, Tori; Romberg, Anders; Henze, Thomas; Santoyo-Medina, Carme; Feys, Peter (International journal of environmental research and public health, 2020)
Goal setting is a core component of physical therapy in multiple sclerosis (MS). It is unknown whether and to what extent goals are set at different levels of the International Classification of Functioning, Disability and Health (ICF), and whether, and to which, standardized outcome measures are used in real life for evaluation at the different ICF levels. Our aim was to describe the real-world use of goal setting and outcome measures in Europe. An online cross-sectional survey, completed by 212 physical therapists (PTs) specialized in MS from 26 European countries, was conducted. Differences between European regions and relationships between goals and assessments were analyzed. PTs regularly set goals, but did not always apply the Specific, Measurable, Achievable, Realistic, Timed (SMART) criteria. Regions did not differ in the range of activities assessed, but in goals set (e.g., Western and Northern regions set significantly more goals regarding leisure and work) and outcome measures used (e.g., the Berg Balance Scale was more frequently used in Northern regions). Quality of life was not routinely assessed, despite being viewed as an important therapy goal. Discrepancies existed both in goal setting and assessment across European regions. ICF assists in understanding these discrepancies and in guiding improved health-care for the future.
Keywords: multiple sclerosis; questionnaire survey; průzkumy a dotazníky; Europe; techniky fyzikální terapie; Disability Evaluation; průřezové studie; Surveys and Questionnaires; Goals; lidé; Multiple Sclerosis; hodnocení výsledků zdravotní péče; Evropa; Physical Therapy Modalities; roztroušená skleróza; cíle; measures; mezinárodní klasifikace funkčních schopností, disability a zdraví; cluster analysis; Cross-Sectional Studies; posuzování pracovní neschopnosti; international classification of functioning, disability and health; physical therapy; International Classification of Functioning, Disability and Health; goals; Outcome Assessment, Health Care; Humans